Recommendations for increasing the motivation of medical staff on the example of the regional clinical hospital - Monika Grabowska; Daria Kolesnyk; Olha Matlai (Health Economics and Management Review)
This article discusses different aspects of increasing the motivation of health workers. The study’s main purpose is theoretical knowledge about the practices of increasing the motivation of health workers. Systematization of literary systems and approaches to solving the problem Increasing the motivation of nurses using the Sumy Regional Clinical Hospital example indicates that the problem arose relatively long ago and scientists are looking for different ways to solve the problem. The urgency of solving this scientific problem lies in the fact that modern research methods are used and modern methods of solving the situation are proposed. Research of the topic Increasing the motivation of medical staff using the example of the General Clinical Hospital in the article is carried out in the following article: relevance of the problem, literature analysis, research results based on an anonymous questionnaire survey of the medical staff using the example of the Sumy Regional Clinical Hospital, recommendations for improvement, conclusions. The study was conducted using an anonymous survey of employees of the regional clinical hospital’s neurological department in 2020. The research object is the relationships within the working collective of the neurological department, which are manifested in the improvement of the system of motivation of health workers. The article presents an empirical analysis of an anonymous survey, which showed the main gaps in the social work of the team of the neurological department. The study empirically confirms and theoretically proves that it is necessary to maintain the balance of psychological and economic agents and the main problem of employee dissatisfaction. The results of a study to improve medical staff’s motivation using the example of a regional clinical hospital can be useful for heads of departments, different directions in medicine, and methodologists for working with teams